Dietary Fiber and Survival in Women with Breast Cancer: A Dose-Response Meta-Analysis of Prospective Cohort Studies. (18th August 2021) - Jayedi, Ahmad; Emadi, Alireza; Khan, Tauseef A.; Abdolshahi, Anna; Shab-Bidar, Sakineh
Abstract: We aimed to investigate the association of dietary fiber consumption with mortality risk in women with breast cancer. A systematic search was undertaken in PubMed, Scopus, and ISI Web of Science till March 2020 to find cohort studies investigating the association of dietary fiber consumption with mortality risk in women with breast cancer. A random-effects model was used to combine study-specific results. The quality of evidence was rated by NutriGrade score. Seven prospective cohort studies with 1, 426 cases of all-cause mortality and 679 cases of breast cancer-specific mortality among 11, 295 patients with breast cancer were included. The relative risks for the highest compared to the lowest category of dietary fiber consumption were 0.63 (95%CI: 0.52, 0.77; I 2 = 0%, n  = 5) for all-cause mortality, and 0.72 (95%CI: 0.54, 0.96; I 2 = 0%, n  = 5) for breast cancer-specific mortality. There was a strong linear association between fiber intake and all-cause mortality risk. The quality of evidence was rated moderate for all-cause mortality, and low for breast cancer-specific mortality. Higher dietary fiber consumption may improve survival in patients with breast cancer. More research is needed to confirm the present results, considering types of fiber consumed and tumor estrogen receptor status.